Menopausal Status and Lung Function among Female Tobacco Factory Workers - Rumman Karimah; Madha Qoyyulledy Tursina; Ida Srisurani Wiji Astuti; Ayu Munawaroh Aziz (GLOBAL HEALTH SCIENCE GROUP, 2025)
Tobacco factory workers face significant occupational health risks, particularly with respect to respiratory function. Female workers may be especially vulnerable to physiological factors, including hormonal status. Objective: To investigate differences in forced expiratory volume in 1 s (FEV1) between menopausal and reproductive-aged women working in tobacco factory production sectors and assess associated risk factors. Methods: This cross-sectional study involved 30 female tobacco factory workers (15 menopausal and 15 reproductive) in Jember, Indonesia. Pulmonary function was assessed via spirometry to measure FEV1. Participant characteristics, including age, work duration, and use of respiratory protective equipment, were collected. The data were analyzed via independent t tests and risk assessment calculations. Results: Menopausal women had significantly lower FEV1 values (67.33 ± 14.351%) than reproductive-age women did (79.13 ± 6.346%; p = 0.007). Overall, 60% of the participants exhibited varying degrees of airway obstruction. Compared with reproductive-aged workers, menopausal workers had a threefold greater risk (OR = 3.143) of developing lung obstruction. Notably, 76.67% of workers reported never using respiratory protective equipment. Conclusions: Menopausal status significantly affects respiratory function among female tobacco factory workers, with a combination of occupational exposure and hormonal changes potentially accelerating lung function decline. These findings emphasize the need for enhanced occupational health measures, particularly for menopausal workers in tobacco production facilities.